38‐1: Invited Paper: Recent Progress in Video Electronic Paper Displays based on Electro‐fluidic Technology. Issue 1 (May 2017) - Deng, Yong; Tang, Biao; Henzen, Alexander Victor; Zhou, Guofu (G.F.)
Abstract : Electronic paper display based on electro‐fluidic technology is one of the most promising reflective displays with full color, video capability and flexibility. In this paper I will give an overview on the recent progress on this technology, in particular new developments of materials, processing, modeling, driving, flexibility and industrialization.